Licensing technology and foreclosure in contests - Derek Clark; Øystein Foros; Jan Yngve Sand (The University of Manchester, Manchester Business School, 2008)
We consider an industry where one firm with a superior technology competes for market shares with several rivals. The owner of the superior technology (the dominant firm) can license or transfer the source of its dominance to a subset of rivals. Allowing the non-license takers to remain active in the market is a drain on the profit of the insiders, and we demonstrate that the dominant firm will only make a transfer of the superior technology if it can be used to foreclose some rival firms. Foreclosure of a subset of firms may thus be the outcome even without restrictions on the licensing schemes. Moreover, we show that when licensing is profitable, the dominant firm will prefer a complete transfer even if a partial transfer can be made.
Keywords: D21; L24; 330; licensing; foreclosure; contest; Technologietransfer; Wettbewerbsvorteil; Marktmacht; Wettbewerbstheorie; Theorie